2019
DOI: 10.1002/bdr2.1477
|View full text |Cite
|
Sign up to set email alerts
|

Differentially sensitive neuronal subpopulations in the central nervous system and the formation of hindbrain heterotopias in ethanol‐exposed zebrafish

Abstract: Background A cardinal feature of prenatal ethanol exposure is CNS damage, resulting in a continuum of neurological and behavioral impairments that are described by the term Fetal Alcohol Spectrum Disorders (FASD). FASDs are variable and depend on several factors, including the amount, timing and duration of prenatal ethanol exposure. To enhance interventions for CNS dysfunction, it is necessary to identify ethanol-sensitive neuronal populations and expand the understanding of factors that modify ethanol terato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“…Whereas embryonic EtOH exposure is found to reduce whole‐brain levels of dopamine and serotonin in zebrafish (Buske and Gerlai, ), as well as reduce the number of cells expressing the pan‐neuronal marker elavl3:gfp (Buckley et al., ) and HuC + neurons in spinal cord (Joya et al., ), effects similarly observed in children with FASD (Riikonen et al., ) and rodents (Gil‐Mohapel et al., ; Livy et al., ), our results here in the AH reveal a very different effect, with 0.5% EtOH exposure found to increase the number of hcrt neurons, not only at 24 to 28 hpf but also at 30 hpf, 3 dpf, and 6 dpf. This stimulatory effect of low‐dose EtOH on the neurogenesis of orexigenic neuropeptides is consistent with our prior reports in both zebrafish (Sterling et al., ) and rodents (Chang et al., , ) and with another study showing EtOH consumption in rats to increase preproorexin mRNA in the lateral hypothalamus (Lawrence et al., ).…”
Section: Discussionmentioning
confidence: 42%
“…Whereas embryonic EtOH exposure is found to reduce whole‐brain levels of dopamine and serotonin in zebrafish (Buske and Gerlai, ), as well as reduce the number of cells expressing the pan‐neuronal marker elavl3:gfp (Buckley et al., ) and HuC + neurons in spinal cord (Joya et al., ), effects similarly observed in children with FASD (Riikonen et al., ) and rodents (Gil‐Mohapel et al., ; Livy et al., ), our results here in the AH reveal a very different effect, with 0.5% EtOH exposure found to increase the number of hcrt neurons, not only at 24 to 28 hpf but also at 30 hpf, 3 dpf, and 6 dpf. This stimulatory effect of low‐dose EtOH on the neurogenesis of orexigenic neuropeptides is consistent with our prior reports in both zebrafish (Sterling et al., ) and rodents (Chang et al., , ) and with another study showing EtOH consumption in rats to increase preproorexin mRNA in the lateral hypothalamus (Lawrence et al., ).…”
Section: Discussionmentioning
confidence: 42%
“…Studies with postconception ethanol generally reveal an inhibitory effect on neuronal development. This is shown in zebrafish by reduced number of HuC + neurons in spinal cord (Joya et al, 2014) and of cells expressing the pan-neuronal marker elavl3:gfp (Buckley et al, 2019) and reduced expression of the neural progenitor marker sox2 as well as HuC + and mature glial marker myelin-associated glycoprotein (Yin et al, 2014), results consistent with reports in children with fetal alcohol spectrum disorders (Riikonen et al, 2005) and rodents (Livy et al, 2003;Gil-Mohapel et al, 2010). Our observation here of preconception maternal ethanol consumption, showing no change in total number of differentiated neurons in HuC:GFP offspring along with an increase in hcrt neurogenesis, suggests that ethanol exposure before conception may affect specific, but not all, neuronal subpopulations during early development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies showing postconception ethanol exposure to stimulate the neurogenesis of hcrt neurons (Chang et al, 2012;Sterling et al, 2016) while sometimes reducing overall neurogenesis (Gil-Mohapel et al, 2010;Buckley et al, 2019), we examined using live imaging in 28 hpf offspring of adult female zebrafish whether maternal consumption for 14 days of 10% ethanol-gelatin before conception alters the total number of differentiated neurons in HuC:GFP transgenic offspring and the number of hcrt neurons in transgenic hcrt:EGFP offspring. Compared to 545 ± 7.3 HuC + neurons detected in control animals at 28 hpf, we found that the offspring from the 10% ethanol-gelatin group had a similar number, an average of 542 ± 13.4 HuC + neurons, showing no significant difference (t( 18 ) = 0.2, ns) (Fig.…”
Section: Preconception Maternal Ethanol Consumption Stimulates Neurogenesis Specifically Of Hcrt Neuronsmentioning
confidence: 99%
“…While a 0.23 BAC dose is high, it is still physiologically relevant, since humans are capable of achieving much higher alcohol levels (Canfield, Forster, Cheong, & Cowan, 2019; A. W. Jones, 2008; Whaley, Young, & Gaynor, 2019). Work in zebrafish and other fish species has also shown media doses lower than 1% v/v impact embryonic development (Buckley, Sidik, Kar, & Eberhart, 2019; Dlugos, Brown, & Rabin, 2011; Dlugos & Rabin, 2003; Flentke et al, 2014; Gerlai, Ahmad, & Prajapati, 2008; Li et al, 2007; E. Loucks & Carvan, 2004; Oxendine et al, 2006; Reimers et al, 2004; Wang et al, 2006). Taken together, the data suggest that zebrafish researchers can generate target ethanol tissue concentrations that replicate human ethanol levels.…”
Section: Ethanol Exposure Paradigms: How Much Do Zebrafish “Drink”?mentioning
confidence: 99%
“…For example, ethanol exposure from gastrulation to pharyngeal stages (6–24 hr post fertilization [hpf]) disrupts formation of the mid‐hindbrain boundary (C. Zhang et al, 2013; Zhang, Anderson, & Cole, 2015) and reduces the number of elavl3‐positive neural progenitors (Joya, Garcia‐Algar, Vall, & Pujades, 2014). Using transgenic lines that label unique CNS neurons, Buckley et al (2019) found migration of facial branchial motor neurons to be ethanol sensitive. Additionally, the branching of secondary motor neurons increased and the diameter of Mautner axons decreased due to ethanol exposure (Shan, Boutin, Ferdous, & Ali, 2015).…”
Section: Zebrafish Insights Into Ethanol Teratogenicitymentioning
confidence: 99%